Meet the ‘headstrong historian’ bringing Africa’s past to life – for Africans - Kimeu, Caroline (The Guardian, 2023)
A visit to Nairobi’s archives led to a ‘eureka moment’ for Kenyan Chao Tayiana. She set out to retell colonial narratives – using digital technology to bring lost and suppressed stories to light.
Kenya
Keywords: 2023-07 July; Africa; Colonialism; Global development; History; Kenya; Rail transport; Uganda